TINDAK TUTUR PERMINTAAN DALAM BAHASA INDONESIA STUDI KASUS PENUTUR BAHASA MELAYU RIAU PADA RANAH KELUARGA DI PEKANBARU - Evizariza, Evizariza (Jurnal Ilmu Budaya, 2008)
The objective of this study is to decribe speech acts of request in Indonesia uttered by the speakers of Bahasa Melayu Riau in family domain in Pekanbaru, to investigate ways of expressing the speech acts and to elaborate politeness as reflected in the speech acts. The data were collected from recordings of interaction and articipant observation in the families of lectures, teachers, civil servants and businessman in Pekanbau. The speech acts are divided into direct and indirect ones. The methods in analyzing the data are the distribusional method and the segmenting immediate constituents techniques such as permutation, subtitution, paraphrase, deletion, and inseretion techniques were used. Additionally, pragmatic (equevalence) method was also used. The findings indicate that there were eleven patterens in the verbal activities. They are: (1) impertive, (2)explicit performative, (3) hedged pervormative, (4) must proposition, (5) doubtness, (6) conditional, (7) impersonal promosition, (8) argumentative, (9) irony, (10) implicit, (11) joking. The first two patterns are categorized as direct patteren serving as literal, while the rest are indeirect patterens servings as no-literal.